2013
DOI: 10.1902/jop.2012.120400
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized, Double‐Masked Clinical Trial Comparing Four Periodontitis Treatment Strategies: 1‐Year Clinical Results

Abstract: Metronidazole had a significant, adjunctive effect in patients with a metronidazole-sensitive subgingival microbiota on the clinical parameters of CAL, PD, and absence of pockets ≥5 mm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
116
1
9

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(129 citation statements)
references
References 59 publications
3
116
1
9
Order By: Relevance
“…Analysis of the abstracts resulted in 95 potential articles. In the third phase, the full text articles of the remaining 95 articles were evaluated, of which 40 did not pass the inclusion criteria (Table ). Another 12 articles were excluded because they were about patients with aggressive periodontitis.…”
Section: Resultsmentioning
confidence: 99%
“…Analysis of the abstracts resulted in 95 potential articles. In the third phase, the full text articles of the remaining 95 articles were evaluated, of which 40 did not pass the inclusion criteria (Table ). Another 12 articles were excluded because they were about patients with aggressive periodontitis.…”
Section: Resultsmentioning
confidence: 99%
“…The data originate in an intervention trial carried out among 184 patients with severe chronic periodontitis (Preus, Gjermo, & Baelum, ; Preus, Gunleiksrud, Sandvik, Gjermo, & Baelum, ; Preus et al., ). The study protocol was approved by the Privacy Ombudsman for the Norwegian Universities (#15768) and Regional Committee for Medical Research Ethics (Oslo, Norway) (REC South East 2.2006.3573/S‐06458b ) .…”
Section: Methodsmentioning
confidence: 99%
“…Details on trial design, measuring techniques and clinical conduct can be found in Preus et al. (, , ).…”
Section: Methodsmentioning
confidence: 99%
“…The obvious distortion problem-especially with radiographs from the maxillary teeth [14]- its confirmation in clinical trials of comparative nature [15, 16], and the call for techniques that could correct for such distortions [15, 16], especially regarding an ongoing longitudinal clinical intervention study [23], prompted the development of the presented digital tool. It is clearly no more than a digital, more versatile version of the Schei ruler [24, 25] and Björn’s technique [26, 27] that at present may be more useful in research, i.e., longitudinal studies where radiographic images are obtained more than once over several years.…”
Section: Discussionmentioning
confidence: 99%